THE INFLUENCE OF PERSONALITY TOWARD ENGLISH PROFICIENCY OF FIB ENGLISH STUDY PROGRAM STUDENTS YEAR 2013 - HANIDA, MAHZUMI AHMAD (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key words: Foreign language learning, personality, extraversion/introversion,neuroticism, temperament Personality potentially determines an individual language learning at advantages or the opposite. Personality in this particular study refers to four classifications by level of extraversion and neuroticism of Eysenck (1947) theory. Later the classification known as temperament. Thus this study is conducted in order to investigate the influence of personality toward English, as foreign language, proficiency. There are two issues which determine how the study is conducted; (1) What is the individual temperament of the FIB students 2013 (2) How is the correlation of each individual temperament toward basic four learning skills on the process of foreign language learning.Using quantitative approach, this study uses data in form of numbers. The instrument of the study is questionnaire of Eysenck Personality Inventory or EPI. The instrument is used regarded as the most appropriate to classifies personality into four types of temperament and the reliability of the instrument, using Cronbach’s alpha, wasestimated at an alpha level of 0.837 at Nodoushan (2011). This study involved 47students as sample of population which all of them are students of English StudyProgram year 2013.The study identifies FIB students 2013 temperaments. Choleric noted on 23 students, 15 found as Sanguine, 2 found as Phlegmatic, and 7 found as Melancholic. The correlations are found between temperaments and the courses. Moreover the researcher finds significant correlation value between courses Understanding LongerTalk toward Cholerics, Sanguine, and Melancholic. Then another significant correlation value is Critical Reading toward Choleric and Sanguine. Based on the findings, the first and second hypotheses are accepted.To extend the study, the researcher suggests next researcher to describe further the influence using different theory, method, inventory, or even data. Thus the similar studies will provide beneficial references related not only to future research but alsodeveloping suggestions of learning management.